Enhanced reading comprehension achieved by training in making inferences - Ripoll Salceda, Juan Cruz; Aguado Alonso, Gerardo (Pulso. Revista de educación, 2007)
This article is about an experience on improving reading comprehension of 2nd grade students of Secondary School attending the subject Basic Linguistic Skills (Spanish language). The implementation of this experience was based on the training in construction of inferences. This approach has been scarcely used at school, although its theoretical and experimental basis is very remarkable. First, theoretical foundations of training in construction of inferences are introduced. Then, a description of the planned tasks adapted for its use with students of Secondary School is included. After that, intervention was evaluated. The results showed that the group of students in the program improved their reading comprehension in relation to the group who was not included in the program. Nevertheless the difference reached no significance, probably because of the short time of program implementation.